Brazil in Pisa 2003 and 2012: students and mathematics - Pereira, Cátia Maria Machado da Costa (2020)
This study presents an investigation on the performance of Brazilian students in Mathematics in Pisa 2003 and 2012. Our goal was to identify the assessed content in which the students had their best performance and most significant dispersion in the scale of assessment levels. Our empirical study consisted of descriptive and comparative analyses. Reports from Inep (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira) and OECD/Pisa were analyzed to make up the database for comparing the two editions of the test. The results show that Brazilian students had their best performance and most significant distribution on the Pisa scale in Indetermination and Data or Probability. However, the performance of Brazilian students, influenced by innumerous factors, is still far below OECD levels.